Respuesta :
Answer:
4u^2 + 16u + 15
Step-by-step explanation:
Multiply each of the terms in the first binomial by each of the terms of the second binomial (4 multiplications in all).
(2u + 3)(2u + 5) = (2u)(2u + 5) + 3(2u + 5)
= (2u)(2u) + (2u)(5) + 3(2u) + 3(5)
= 4u^2 + 10u + 6u + 15
= 4u^2 + 16u + 15
Answer:
16u²+15
Step-by-step explanation:
You will use the equation in the first bracket to multiply both of the equations. You'll have
2u(2u+3)+3(2u+5)
4u²+6u+6u+15
4u²+12u+15
16u²+15
That will be your final answer.
IF THIS HELPS PLS MARK ME AS BRAINLIEST. THANKS